Oxidation of propane to acrylic acid and acetic acid over alkaline earth-doped Mo-V-Sb-O-x catalysts - Chaudhari, Chandan S.; Sable, Shailesh S.; Gurav, Hanumant; Kelkar, Ashutosh A.; Rane, Vilas H. (Journal of Natural Gas Chemistry, 2010)
Alkaline earth metal (Mg, Ca, Sr and Ba)-doped Mo-V-Sb-O-x catalysts, prepared by a dry-up method, have been investigated for their catalytic performance in the oxidation of propane under different reaction conditions. The catalysts have been characterized by N-2 adsorption-desorption, temperature-programmed desorption (TPD) of NH3, SEM and XRD. Influence of water vapor on the catalytic performance, particularly on the selectivities to acetic acid and acrylic acid, has also been studied. The selectivity to acrylic acid was improved significantly by the doping of alkaline earth metals to Mo-V-Sb-O-x catalysts. The surface acidic sites of the catalyst decreased with the doping of the catalyst with alkaline earth metals, which ultimately was found to be beneficial for obtaining high selectivity to acrylic acid. The catalytic activity and product selectivities were found to be influenced by the reaction temperature, C3H8/O-2 ratio and space velocity. A significant improvement in the selectivity to acrylic acid has also been observed by the addition of water vapor in the feed of propane and oxygen in the oxidation of propane.
Keywords: Acetic acid; acrylic acid; alkaline earth doped Mo-V-Sb-O-x catalysts; oxidation of propane; Surface acidity

Synthesis of ethyl acetate by esterification of acetic acid with ethanol over a heteropolyacid on montmorillonite K10 - Gurav, Hanumant; Bokade, Vijay V. (Journal of Natural Gas Chemistry, 2010)
In present work, liquid phase esterification of acetic acid with ethanol over dodecatungestophosphoric acid (DTPA) supported on K10 mommorillonite was systematically studied and optimization of process parameters was carried out The 20% m/m urpAtK tO was found to be the optimum catalyst with 90% acetic acid conversion and 100% ethyl acetate selectivity The study was also explored to see the feasibility of 20% m/m DTPA/K10 as a catalyst for the alkylation of acetic acid with other alcohols like methanol, iso-propanol and sr-butanol. The 20% m/m DTPA/K10 has shown increased activity with the increase in carbon number, at the same alcohol reflux The results are novel
Keywords: Acetic acid; Ethanol; ethyl acetate; Heteropolyacid; montmorillonite K10